STUDY EKSPERIMENTAL PERILAKU ALIRAN FLUIDA PADA SAMBUNGAN BELOKAN PIPA - Hariyono, Hariyono; Rubiono, Gatut; Mujianto, Haris (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2016)
Pipe network is common instalation in daily life. Elbow is a component in pipe network.This research is aimed to get fluida flow behavior in elbow. The experiment is conduct with fluid flow apparatus with number of elbows. The apparatus consist ¾ inch diameter of PVC pipe and a pump which generate water flow and pressure. Volume flow rate is vary by valve opening which are ¼, ½, ¾ and full open. The flow rate is measured using flow meter and a stopwatch.This flow rate is used to get Reynold number. The pressure before and after elbow are measured using U tipe manometer. The measurement takes 5 times at 5 measurement points. The result shows that fluid flow tend to have pressure decreasing. Much elbow number caused greater pressure decreasing. The maximum pressure occur at Re 3049,60 at first point measurement which is592,52 kg/m2. The minimum pressure occur at Re 1532,45 at fifth point measurement which is 8,18 kg/m2.